Advances in Medical Robotics: Surgical Automation and Rehabilitation Systems - Ashutosh Kushwaha (International Journal of Advanced Robotics and Automation Technology, 2025)
Medical robotics has emerged as a groundbreaking technology, transforming modern healthcare through advancements in surgical automation and rehabilitation systems. Robotic-assisted procedures machine learning (ML), and artificial intelligence (AI) have all been used to improve patient recovery consequences, reduce invasiveness, and increase surgical precision. These developments have redefined traditional medical techniques by opening the door for more effective, precise, and tailored therapies. By improved dexterity, stability, and vision, surgical robots has transformed minimally invasive techniques and given surgeons greater influence over intricate surgeries. Patients who experience robotic-assisted procedures, including those carried out with the da Vinci Surgical System, cite fewer problems, shorter hospital stays, and easier recovery periods. Additionally, AI-powered robotic platforms are now capable of assisting in preoperative planning, intraoperative guidance, and postoperative assessments, further optimizing surgical efficiency. Robotic advances in rehabilitation have substantially improved the quality of life for people mending from musculoskeletal disabilities, injuries to the spine, and neurological disorders. Robotic exoskeletons and assistive devices help restore mobility, enhance motor functions, and promote faster rehabilitation through real-time adaptive support and patient-specific therapy. The integration of ML algorithms enables these systems to personalize treatment strategies, ensuring better outcomes for individuals undergoing physical therapy. Notwithstanding these outstanding developments, obstacles including exorbitant prices, moral dilemmas, obtaining governments permissions, and the requirement for specific training prohibit broad acceptance. Furthermore, ensuring the seamless interaction between robotic systems and human professionals remains a critical area of ongoing research. This review delves into the latest developments in medical robotics, analyzing the impact of AI-driven automation in surgery and rehabilitation. It also discusses existing challenges and future prospects, highlighting the potential of robotics to further revolutionize patient care and redefine the standards of modern medical practice.
Keywords: artificial intelligence in healthcare; exoskeleton technology; medical robotics; rehabilitation robotics; robot-assisted surgery; surgical automation